The initial and lingering impact of coronavirus disease 2019 (COVID-19) on catheter-associated infections in a large healthcare system in New York City - Jevon Samaroo-Campbell; Wenqi Qiu; Habtamu Asrat; Marie Abdallah; Mary Fornek; Briana Episcopia; John Quale (Cambridge University Press, 2022)
Catheter-related infections increased during surges of coronavirus disease 2019 (COVID-19) in an 11-hospital system in New York City. A disproportionate number of central-line infections occurred in larger hospitals. Patients with COVID-19 had shorter times from catheter insertion to infection and a higher incidence of infections with enterococci.